Functional Outcome of Open Latarjet Procedure for Recurrent Anterior Shoulder Dislocation - Muhammad Siraj; Qaisar Azim; Ahsan Sajjad; Awal Hakeem (Gandhara University, 2023)
OBJECTIVES To find the functional outcome of the open Latarjet method for recurrent anterior shoulder dislocation. METHODOLOGY The current retrospective study was conducted at the Orthopedic and Trauma Department of the Khyber Teaching Hospital in Peshawar from September 2020 to August 2021. A total of 31 patients were included in the study, of which 29 were males and 2 were females. A detailed medical history was obtained through physical examination, and all necessary laboratory tests were requested. AP and axillary views of plain X-ray radiographs were taken. We used a CT scan on all the patients to calculate the humeral and glenoid bone loss. We had all patients undergo an MRI to rule out soft tissue pathology. Six months after surgery, the outcome was graded using the Constant Murley Score on a good, good, fair, and poor scale. RESULTS In this study open Latarjet procedure was done in 31 patients with 29 males (93.4%) and two females (6.45%). The right-sided shoulder was involved in 24 (77.14 %) patients, while the left shoulder was involved in 7 patients (22.58%). A bipolar lesion in the shoulder with bone loss was seen on the glenoid side at 17.5% (range 10-25%), and the humeral side was 22.5%. Follow-up was done for six months in which 22 patients had a very good outcome (70.96%), six patients had a good outcome(19.35%), two patients had a fair outcome(6.45%), and one patient had a poor outcome(3.22%). There were no major complications seen like graft fractures, graft  malposition, neurovascular compromise, and hardware breakage CONCLUSION Recurrent anterior shoulder instability can be effectively treated with open Latarjet with excellent functional outcomes and a very low complication rate and recurrence.